2021
DOI: 10.1186/s12885-021-07940-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequent high-risk HPV co-infections excluding types 16 or 18 in cervical neoplasia in Guadeloupe

Abstract: Background Cervical cancer is the fourth cancer worldwide. The Human Papilloma Virus is responsible for 99% of the cases but the distribution of its genotypes varies among populations. We aimed to identify HPV genotypes distribution in women with grade 2/3 cervical intraepithelial dysplasia or invasive cervical cancer in Guadeloupe, a French Caribbean territory with a population mainly of African descent. Methods We used paraffin-embedded tumors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Associations between cervical lesions and infection with HR-HPV other than genotypes 16 or 18 are also notable in the study by Gaete et al [ 29 ] on 213 samples of cervical pathology with a diagnosis of dysplasia or cancer in which 31 is found to be the number one genotype at 47%, followed by genotypes 33 , 16 , 44 , and 28 .…”
Section: Discussionmentioning
confidence: 80%
“…Associations between cervical lesions and infection with HR-HPV other than genotypes 16 or 18 are also notable in the study by Gaete et al [ 29 ] on 213 samples of cervical pathology with a diagnosis of dysplasia or cancer in which 31 is found to be the number one genotype at 47%, followed by genotypes 33 , 16 , 44 , and 28 .…”
Section: Discussionmentioning
confidence: 80%
“…In one of our previous studies, we found that HPV detected in cervical swabs is high-risk, while low-risk HPV is mainly found in vaginal and rectal swabs, and multiple subtypes of infection are common (33). Some studies have found that HPV44 is one of the common types in tumor tissues of cervical cancer patients (51), frequently detected in human intestines (52,53). Women might not be mainly high-risk types in the early stage of HPV infection, and several low-risk types of HPV might also play an important role in early infection.…”
Section: Discussionmentioning
confidence: 83%
“…In one of our previous studies, we found that HPV detected in cervical swabs is high-risk, while low-risk HPV is mainly found in vaginal and rectal swabs, and multiple subtypes of infection are common [ 38 ]. Some studies have found that HPV44 is one of the common types in tumor tissues of cervical cancer patients [ 56 ], frequently detected in human intestines [ 57 , 58 ]. Studies have shown that HPV81 is detected in the majority of women with cervical cytological abnormalities and is associated with precancerous and cancerous lesions [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%